Factors associated with the use of dental health services - Dho, María Silvina (2018)
This paper seeks to analyze the factors associated with the use of dental health services (UDHS) by adults in the city of Corrientes, Argentina. A cross-sectional study was conducted. Information concerning the study variables was collected via a home survey. The sample size was established with a 95% confidence interval level (381 individuals). A simple random sampling design was used, which was complemented with a non-probability quota sampling. The data was analyzed using SPSS version 21.0 and Epidat version 3.1 softwares. Socio-economic level, dental health coverage, perception of oral health care, perception of oral health, knowledge about oral health, and oral hygiene habits were significantly associated with the UDHS over the last twelve months. These same factors, excluding dental health coverage and knowledge about oral health, were associated with the UDHS for routine dental check-ups. Measures should be implemented to increase the UDHS for prevention purposes in men and women of all socio-economic levels, particularly in less-privileged individuals.